Chilaiditi Syndrome: A Case Report Highlighting the Intermittent Nature of the Disease - Esha M. Kapania; Christina Link; Joshua M. Eberhardt (Case Reports in Medicine)
Background. Chilaiditi syndrome is a phenomenon where there is an interposition of the colon between the liver and the abdominal wall leading to clinical symptoms. This is distinct from Chilaiditi sign for which there is radiographic evidence of the interposition, but is asymptomatic. Case Presentation. Here, we present the case of a patient who, despite having clinical symptoms for a decade, had a delayed diagnosis presumably due to the interposition being intermittent and episodic. Conclusions. This case highlights the fact that Chilaiditi syndrome may be intermittent and episodic in nature. This raises an interesting question of whether previous case reports, which describe complete resolution of the syndrome after nonsurgical intervention, are perhaps just capturing periods of resolution that may have occurred spontaneously. Because the syndrome may be intermittent with spontaneous resolution and then recurrence, patients should have episodic follow-up after nonsurgical intervention.